2021
DOI: 10.3390/polym13203458
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Cage-Type Polyglycolic Acid/Collagen Nanofiber Blend with Improved Surface Wettability and Handling Properties for Potential Biomedical Applications

Abstract: Electrospun biobased polymeric nanofiber blends are widely used as biomaterials for different applications, such as tissue engineering and cell adhesion; however, their surface wettability and handling require further improvements for their practical utilization in the assistance of surgical operations. Therefore, Polyglycolic acid (PGA) and collagen-based nanofibers with three different ratios (40:60, 50:50 and 60:40) were prepared using the electrospinning method, and their surface wettability was improved u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Furthermore, the fracture surface morphology of FGD particles in the composites has significantly changed from that of their prior SEM images. 58,59 The surface morphology of the original FGD particles is rough and porous. A layer of XSBR fills the pores and covers the entire particle surface tightly in the composites, smoothing the coarse surface of the FGD particles.…”
Section: Micromorphology Of Xsbr/fgd Compositesmentioning
confidence: 99%
“…Furthermore, the fracture surface morphology of FGD particles in the composites has significantly changed from that of their prior SEM images. 58,59 The surface morphology of the original FGD particles is rough and porous. A layer of XSBR fills the pores and covers the entire particle surface tightly in the composites, smoothing the coarse surface of the FGD particles.…”
Section: Micromorphology Of Xsbr/fgd Compositesmentioning
confidence: 99%
“…97 As a result, there are still hurdles in simplifying the synthesis approach, enhancing recycling and flame retardant efficiency, suggesting appropriate routes for various requirements, and increasing biodegradability and nontoxicity. 117,118 Moreover, the reversible dynamic covalent bonds in RFRs have a lower bond energy than traditional covalent bonds, which indicates that the thermal stability and chemical resistance of the materials will suffer significantly. 119 Sometimes, thermoset recycling processes are relatively difficult to achieve, such as light induction or long times of high temperature and pressure.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Additionally, assessing the ecological hazard and biodegradability of RFRs would be an intriguing new study area in the upcoming years. 117,118 Another option is to change the synthesizing process to improve recycling and fire resistance. One study possibility is the efficient synthesis of dynamic bonds and more aromatic structures with P-N-Si, P-Si-B, and P-N-B incorporating fire retardants that can perform in both condensed and gaseous phases while also being recyclable.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…21 El-Ghazali et al revealed that fiber diameter can affect cell infiltration behavior. 22 Normally, MEW scaffolds are designed with homogeneous porosity or microarchitecture, which is conducive to maintaining consistent cell performance and conducting monoculture studies. 18 However, internal architectures vary in different regions of biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al showed scaffolds with aligned fibers can regulate the differentiation of stem cells and even promote tendon repair 21 . El‐Ghazali et al revealed that fiber diameter can affect cell infiltration behavior 22 …”
Section: Introductionmentioning
confidence: 99%